Successful Treatment of Cyst Infection in an Infant With Autosomal Dominant Polycystic Kidney Disease Using Trimethoprim/Sulfamethoxazole - Yokoyama, Hiroki; Sakaguchi, Mayumi; Yamada, Yuko; Kitamoto, Koichi; Okada, Shinichi; Kanzaki, Susumu; Namba, Noriyuki (Frontiers in Pediatrics, 2020)
Autosomal dominant polycystic kidney disease (ADPKD) is the most common genetic disease causing renal cysts. Reports on kidney cyst infection in children are rare despite cyst infections being important complications of ADPKD. Here, we report the case of a child without any medical history who had a urinary tract infection with sepsis at 7 months. Leukocyturia persisted despite antibiotic therapy because the infection was treatment-resistant. Initial ultrasound and contrast computed tomography were inconclusive because cysts could not be detected clearly and a family history of renal cysts was not determined. Subsequent history of paternal renal cysts, thick walls in infectious cystic lesions on diffusion-weighted magnetic resonance imaging (MRI), and multiple small lesions with high signals on T2-weighted imaging in both kidneys became apparent. Upon diagnosis of ADPKD with cyst infection, antibiotic therapy was switched from cefotaxime to trimethoprim/sulfamethoxazole (TMP/SMX) to achieve better cyst penetration, which successfully resolved the infection. In this patient, MRI was effective for clear visualization and diagnosis of infectious lesions and small cysts in undiagnosed ADPKD with cyst infection. Administering antibiotics with better cyst penetration is important. TMP/SMX is an option for use in children. This is the first case report that describes ADPKD with cyst infection in an infant in detail.